American private direct investment in the Philippines after independence - Sicat, Gerardo P. (2015)
The Philippines has lagged behind East and Southeast Asian economic growth successes in the course of contemporary times. A historical perspective is presented to explain this lag. When the country entered the definite road to independence from American rule in 1934, it adopted a political Constitution that limited foreign capital to a minority role in three industries – land, public utilities, and the exploitation of natural resources. During the colonial period and after political independence in 1946, American foreign direct investment in the country was dominant and large. This continued after independence as US citizens were granted equal rights of Filipinos and American businesses received war damage payments to rehabilitate their investments. This was further helped by bilateral preferential trade with the United States during twenty-eight years of economic adjustment. In actual practice, the restrictive provisions in the Constitution invited many virulent forms of nationalistic economic policies of exclusions of foreigners in other lines of economic activity and led to inward-looking economic development policies. These policies discouraged American foreign direct investments causing disinvestment in key areas. The restrictive economic provisions in the Constitution continue to this day even as the economy is opening more to world markets.
Keywords: Foreign investments -- Government policy; Economic development; American investments